Accountability vertical: um estudo sobre o controle social exercido pelos Conselhos de Segurança Pública nos bairros da Cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This study aims to analyze how the community councils of public safety (CONSEG) practice vertical accountability, with community policing companies in the city of Manaus. The aim is to answer the following question: how interactive security community councils exert social control as vertical accountability practice in community policing companies in Manaus? To do so, they were raised research to better understand the issue, highlighting: Managerial public management and administrative reform of the Year 1990 in Brazil; social control as controlling tool and accountability; the function of the control of councils in the public security policies in Brazil, accountability; horizontal and vertical accountability accountability and its tools. In the methodology, the study was characterized, as its nature, in a quantitative research; in relation to their goals, as Descriptive; about the procedures, was a field research. The data collection approach used in this research was the survey method with use of a questionnaire and a Roadmap for observation, based on the proposal of terminology Guillermo O'Donnell (1998) and as an analytical method the description of practices and tools that define the vertical accountability as the union of three dimensions: surveillance and control, participation and interaction and accountability and results. As the analysis of the vertical accountability of CONSEG practice, together with the public security organs in the city of Manaus, it was concluded that there is the use of monitoring and control tools, participation and interaction with accountability and results by the CONSEG. You might also note that the use of these tools is very low for a body of external social control to the state. Among the tools analyzed, presented the best use within the councils was the participation and interaction, then accountability and results, and inspection and control. It was concluded that the use of the tools of social control as a practice of vertical accountability in Manaus City CONSEG have apparently ineffective characteristics of social control over public security organs. Despite conclusive results, there is plenty of room for the development of new research in the area on the subject.
Keywords: Segurança Pública; Policiamento comunitário; Políticas Públicas; Gestão Pública; CIENCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO: CIENCIAS CONTABEIS